Research on Three Key Issues of Multimodal Emotion Recognition Technology in Service Robotics Context - Lyu, Junze (Transactions on Computer Science and Intelligent Systems Research, 2025)
With the rapid development of artificial intelligence technology, service robots are increasingly integrating into daily life scenarios. Achieving efficient and natural human-robot interaction has become a key challenge. The ability to recognize emotions, as a core factor in enhancing the interaction experience, has attracted extensive attention from both the academic and industrial communities. This paper focuses on the emotion recognition problem of service robots, analyzes three key problems that need to be solved by the application of multimodal emotion recognition technology in service robots, lists and analyzes several advanced machine learning algorithms that can help solve the problem, evaluates and analyzes them respectively, and summarizes their common limitations as well as the possible improvement methods in the future. This research not only provides crucial theoretical support and algorithmic paths for the emotional computing of service robots, but also helps to build a more reliable human-robot collaboration relationship. It holds significant application value for promoting the real implementation of service robots in real-life scenarios.
Keywords: Service robotics; Multimodal emotional recognition; Zero-sample learning; Sensor-less emotion recognition technology; Macrolanguage model.